Comparison of Functional and Radiological Outcomes of Transforaminal Lumbar Interbody Fusion and Posterolateral Fusion Techniques in the Treatment of Lumbar Spinal Stenosis - Ziroglu, Nezih; Duramaz, Altug; Bayrak, Alkan (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Background This study aimed to compare posterolateral fusion with transforaminal lumbar interbody fusion (PLF + TLIF) and PLF only in terms of revision surgery rates and complications, as well as functional and radiological outcomes in lumbar spinal stenosis (LSS) patients.Methods Seventy-one patients (37 patients in the PLF + TLIF group and 34 patients in the PLF only group) who underwent surgery due to LSS between January 2013 and December 2016 were retrospectively investigated. Functional evaluation was performed by using the McGill-Melzack Pain Questionnaire (MPQ), Roland Morris Disability Questionnaire (RMDQ), and Oswestry Disability Index (ODI) scales pre-and postoperatively. Radiological evaluation was made by examining adjacent vertebrae, posterior ligamentous complex (PLC) morphology, and sagittal balance on magnetic resonance imaging (MRI).Results Postoperative MPQ, RMDQ, and ODI scores were significantly better in the PLF + TLIF group (p < 0.001, p < 0.001, and p = 0.001, respectively). The complication rate was significantly higher in the PLF only group (p = 0.026). In the PLF + TLIF group, postoperative functional scores showed significant improvement in terms of the instrumented segment and level of interbody fusion. Postoperative functional scores showed significant improvement in PLF + TLIF patients with no complications, no revision surgery, no postoperative MRI findings, and neutral sagittal balance compared to the preoperative functional scores (p < 0.001).Conclusion PLF + TLIF is significantly superior in terms of functional scores and complications, despite the statistical similarity in terms of postoperative MRI findings and sagittal balance between the groups. Surgeons should prefer PLF + TLIF for the surgical treatment of LSS for better results.
Keywords: lumbar spinal stenosis; transforaminal lumbar interbody fusion; posterolateral fusion; functional and radiological outcomes